Snowblind - Golden, Christopher (St. Martin's Press, 2014)
"SNOWBLIND is a thrilling contemporary ghost story with both horror and heart. The small New England town of Coventry is haunted by its memories of a deadly winter... in which loved ones were lost, families torn apart, and a town buried in a terrible blizzard. Now, twelve years later, the people plagued by their memories of that storm are haunted once again as a new storm approaches, promising to wreak new havoc. Old ghosts trickle back, and this storm will prove even more terrifying and deadly than the last. With richly textured characters, scarred and haunted by the ghosts of those they loved most, Snowblind reinvents the ghost story for today's world. Spellbinding in scope and rooted deeply in classic storytelling, Christopher Golden has written a chilling masterpiece that is the best work of his career and a standout supernatural thriller"--